Staged construction and settlement of a dam founded on soft clay - Ozcoban, Sukru; Berilgen, Mehmet M.; Kilic, Havvanur; Edil, Tuncer B.; Ozaydin, I. Kutay (ASCE-AMER SOC CIVIL ENGINEERS, 2007)
Alibey Dam is located near Istanbul in Turkey on the Alibey Stream, 4.5 km north of its point of confluence with Golden Horn, an ancient submerged river mouth. It was constructed as an earthfill dam over 30-m-thick soft valley sediments. Before the construction of the dam. field and laboratory tests were performed to determine the geotechnical characteristics of the foundation soils. During the construction and many years after the construction of the earthfill embankments, including the cofferdams and the intermediate fills, the response of the foundation soils was monitored by extensive field instrumentation generating a unique long-term (over 25 years) database. With proper instrumentation and careful monitoring of the collected data, field construction rates could be adjusted and the earth dam was safely constructed on the thick soft deposits. Approaches to settlement prediction were evaluated in a historical context, starting with the simplified one-dimensional approach available at the time of construction to more sophisticated analyses including the employment of modem numerical methods, in terms of the recorded data. Standard subsurface exploration and field testing supplemented with conventional laboratory testing provided the relevant material parameters that were used in the finite element method. The only exception to this was the overall hydraulic conductivity of the deposit, which controlled the rate of consolidation. Early field observations were used to assign the appropriate hydraulic conductivity. An elastoplastic soil model in a coupled analysis of consolidation was employed in the analysis that yielded realistic predictions of field behavior in response to the complex construction history. The accurate prediction and monitoring of the behavior of soft and thick soil layers subjected to staged construction, as in the case of Alibey Dam, is very important for planning of the construction as well as the expected behavior after construction.
Keywords: Engineering; Geology